2020
DOI: 10.1101/2020.07.13.201624
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Histone Methyltransferase SETD2 Modulates Oxidative Stress to Attenuate Colonic Inflammation and Tumorigenesis in Mice

Abstract: BACKGROUND & AIMS: Inflammatory bowel disease (IBD) is a complex and relapsing inflammatory disease, and patients with IBD exhibit a higher risk of developing colorectal cancer (CRC). Epithelial barrier disruption is one of the major causes of IBD in which epigenetic modulation is pivotal. However, the epigenetic mechanisms underlying the epithelial barrier integrity regulation remain largely unexplored. Here, we investigated how SETD2, an epigenetic modifier, maintains intestinal epithelial homeostasis an… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…Liu et al also found that EZH2 promotes the inflammatory response and apoptosis in colitis by modulating the TNFα signaling pathway 14 . In addition, Liu et al reported that SETD2-mediated H3K36me3 can regulate oxidative stress to alleviate inflammation in mice 13 . It is worth pointing out that the role of H3K36me2 in IBD remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al also found that EZH2 promotes the inflammatory response and apoptosis in colitis by modulating the TNFα signaling pathway 14 . In addition, Liu et al reported that SETD2-mediated H3K36me3 can regulate oxidative stress to alleviate inflammation in mice 13 . It is worth pointing out that the role of H3K36me2 in IBD remains unknown.…”
Section: Discussionmentioning
confidence: 99%